Needs Analysis of English for Specific Purpose at Engineering Students in Vocational High School - Mutiara Yulia Efendi; Eka Mayasari; Joko Iswanto; Leni Apriyani (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2025)
English teaching for engineering students is categorized as English for Specific Purposes (ESP). This study aims to determine the English learning needs of the Electrical Power Installation Engineering, Industrial Automation Engineering, Building Modeling and Information Design, and Construction and Property Business departments at SMKN 3 Tanjungpinang. The research method used is descriptive qualitative with questionnaire and interview instruments involving 26 respondents, consisting of 25 students and 1 English teacher. The results of the study indicate that students need to improve their speaking skills, vocabulary, grammar, and pronunciation. Learning methods such as Contextual Teaching and Learning and Task-Based Learning need to be applied to support the learning process. The main difficulties faced are the lack of mastery of speaking and pronunciation, as well as limited vocabulary. Students also like video-based and interactive learning media. The implication is that teachers need to develop more communicative teaching methods and use interesting media so that learning is more effective and relevant to students' needs.